Role of Intravitreal Bevacizumab before Pars Plana Vitrectomy in Patients with Vitreous Hemorrhage Due to Proliferative Diabetic Retinopathy - Umer Kazi, Arif Rabbani, Aimal Khan, Umair Qidwai (Pakistan Journal of Ophthalmology, 2018)
Purpose: To investigate the role of Bevacizumab as an adjunct to the management of patients with proliferative diabetic retinopathy undergoing pars plana vitrectomy. Material and Methods: Hundred and eight eyes of 108 patients with proliferative diabetic retinopathy scheduled for surgery were included in the study. They were randomized to vitrectomy with preoperative IVB (group 1) or standard vitrectomy (group 2). Group 1 underwent a single intra-vitreal injection of bevacizumab 1.25 mg /0.05ml one week prior to vitrectomy. Main outcome measures were best corrected visual acuity (BCVA) after surgery, post-operative complications. Results: Mean age of the patients was 52.07±5.54 years (range 39-67). At 6 months, 40 patients in group 1 had BCVA better than baseline as compared to 24 patients in group 2. In group 1, only one patient had early post-operative vitreous hemorrhage, whereas 22 patients in group 2 had early vitreous hemorrhage. Conclusion: Pre-operative IVB is helpful in improving BCVA post operatively, reducing the time of surgery, decreasing the incidence of intraoperative and postoperative bleeding and reducing the frequency of rubeosis and hyphaema.